Analysis Of Factors Affecting The Amount Of People's Business Credit Loans In Lubuk Pakam District, Deli Serdang Regency, North Sumatra Province - Muhammad Rum Lubis; Reza Nurul Ichsan; Lukman Nasution; Venny Fraya Hartin Nst; Diana Lubis (SEAN Institute, 2024)
The objective of this study was to examine the influence of business tenure, collateral, number of family dependents, customer age, and the presence of an internal control system on bank credit lending practices. The methodology utilized was a quantitative approach, utilizing primary data sources, namely, information obtained directly from the first source. The sample size for this study was 133 respondents, all of whom were customers of KUR loans. A random sampling technique was employed to select the sample, with data collection carried out using a questionnaire. A Structural Equation Modeling with Partial Least Squares (SEM-PLS) approach was then used to analyze the data, with the results of this process then processed through the Smart PLS tools. This entailed examining both the results of the Measurement Model Analysis Test (outer model) and the Model Analysis Test (inner model). The findings revealed a negative association between business tenure and credit lending, with no impact on credit lending. Collateral demonstrated a positive and statistically significant impact on credit lending. Conversely, the number of dependents exhibited a negative correlation with credit lending. Furthermore, customer age demonstrated an inverse association with credit lending, with no impact. The internal control system, however, exhibited a positive and statistically significant influence on credit lending.